The Price Puzzle: Mixing the Temporary and Permanent Monetary Policy Shocks - Ida Wolden Bache; Kai Leitemo (Norges Bank, 2008)
We argue that the correct identification of monetary policy shocks in a vector autoregression requires that the identification scheme distinguishes between permanent and transitory monetary policy shocks. The permanent shocks reflect changes in the inflation target while the transitory shocks represent temporary deviations from the interest rate reaction function. Whereas both shocks may raise the nominal interest rate on impact, the inflation and output responses of the two shocks are different. We show, using a simple simulation experiment, that a failure to distinguish between the two types of shocks can result in a "price puzzle".
hdl:11250/2497767
Keywords: E47; E52; E61; 330; VAR modeling; monetary policy shocks; identification; price puzzle